EU INTEGRATION AND ACCESSION: IMPLICATIONS FOR WEST BALKAN SOVEREIGNTY AND PROCESS OF DEMOCRATIZATION (Journal of Contemporary Studies, 2012)
Abstract This is believed in Southeast Europe that its future and prosperity lies in the EU; the unfolding economic and socio political reforms in the region are based on the impulse for EU membership. The EU continues to direct both economic and political incentives towards making the region ripe for integration and accession. This paper analyzes the increasing impulse for EU membership in the Balkan; brings forth the erosion of state sovereignty for institutional sovereignty, for which political landscape of the region gets changed. The trend is posing equal challenge to the identity of the region and its people, as influence of both domestic and foreign civil society grows. This paper also focuses on the extent of EU inspired reforms among the Balkan states. The intention behind this effort is to be understood. It is to be measured that whether or not this effort is based on state interests in the EU only. If so, the new members can latter return to their old ways of weak governance without democratizing their political systems in essence. For instance, the extent to which EU reform and membership has changed Romania and Bulgaria is arguable.